Long-term outcome of the REMAGUS 02 trial, a multicenter randomised phase II trial in locally advanced breast cancer patients treated with neoadjuvant chemotherapy with or without celecoxib or trastuzumab according to HER2 status. (April 2017) - Giacchetti, Sylvie; Hamy, Anne-Sophie; Delaloge, Suzette; Brain, Etienne; Berger, Frédérique; Sigal-Zafrani, Brigitte; Mathieu, Marie-Christine; Bertheau, Philippe; Guinebretière, Jean Marc; Saghatchian, Mahasti; Lerebours, Florence; mazouni, chafouny; et al.
Abstract: Background: The REMAGUS-02 multicenter randomised phase II trial showed that the addition to neoadjuvant chemotherapy (NAC) of trastuzumab in patients with localised HER2-positive breast cancer (BC) increased the pathological complete response (pCR) rate and that the addition of celecoxib in HER2-negative cases did not increase the pCR rate. We report here the long-term follow-up results for disease-free survival (DFS) and overall survival (OS). Patients and methods: From 2004 to 2007, 340 stage II–III BC patients were randomly assigned to receive neoadjuvant EC-T (four cycles of epirubicin–cyclophosphamide followed by four cycles of docetaxel) +/− celecoxib in HER2-negative cases (n = 220) and ± trastuzumab in HER2-positive cases (n = 120). From September 2005, all patients with HER2-positive BC received adjuvant T (n = 106). Results: Median follow-up was nearly 8 years (94.4 months, 20–127 m). In the HER2-negative subgroup, addition of celecoxib was not associated with a DFS benefit. Favourable factors were smaller tumour size, expression of progesterone receptor status (PgR) and pCR. In the HER2-positive population, neoadjuvant trastuzumab was not associated with a DFS benefit. Axillary pCR was the only prognostic factor associated with DFS in this group [HR = 0.44, 95% CI = 0.2–0.97], p = 0.035]. To note, DFS and OS were significantly higher in the HER2-positive than in HER2-negative BC patients (HR = 0.58 [0.36–0.92], p = 0.021). Conclusion: Celecoxib combined with NAC provided neither pCR nor survival benefit in patients with HER2-negative BC. Absence of PgR is a major prognostic factor. Neoadjuvant trastuzumab increased pCR rates without translation into a DFS or OS benefit compared with adjuvant trastuzumab only. Axillary pCR could be a more relevant surrogate of survival than in the breast in HER2-positive population. A retrospective comparison shows that patients with HER2-positive tumours have a better outcome than HER2-negative BC patients showing the impact of trastuzumab on the natural history of BC. Highlights: Celecoxib, an anti Cox2, does not improve pathological complete response (pCR) nor outcome in HER2 negative breast cancer patients receiving sequential neoadjuvant chemotherapy. Long term outcome of luminal B breast cancer can be worse than triple negative breast cancer while HER2 positive breast cancer patients have a better prognostic than other subtypes with the addition of trastuzumab in neoadjuvant or adjuvant setting. Abstract : Key message : Celecoxib, an anti-Cox2, neither improves pCR nor the outcome in HER2-negative BC patients receiving sequential NAC. The long-term outcome of luminal B BC can be worse than triple-negative BC, whereas HER2-positive BC patients have a better prognostic than other subtypes with the addition of trastuzumab in neoadjuvant or adjuvant setting.